Developing Teachers Skill in Creating Problem-based Learning Tools: Lesson Study-based Research - Rahmah, Mursidah; Fitri Siti Sundari; Yanti Suryanti (International Journal of English Language and Pedagogy, 2023)
The purpose of this study is to describe the teachers’ skill development of creating problem-based learning tools. The subject of this study were 32 students of the PPG study program that has reached the phase of developing teaching and learning tools. The research instruments were an observation sheet, interview, and documentation taken from the lesson plan developed by the students-teacher. The results show a good improvement from cycle one to cycle two. Learning tools consisting of lesson plans, teaching materials, media, LKPD and assessment instruments produced by participants demonstrate the application of collaborative learning models (PBL and PjBL), contextual teaching materials and up-date internet-based learning media (application Word Wall, Quizizz), interesting worksheets and assessment instruments that are in accordance with KD and GPA that have been set at the beginning.